Implementation of Character Based Learning at Sekolah Alam Bireuen (SABIR) - Raihan Hayati; Mukhlesiyeni, Ety; Nurlaili (PGMI IAIN Lhokseumawe, 2025)
Sekolah Alam Bireuen (SABIR) is a new school that focuses on outdoor learning by utilizing nature as a medium for education. This research aims to understand the process of character implementation among students during learning activities at SABIR for grades IV, V, and VI using qualitative research methods. The results of the character implementation process at SABIR consist of two stages: the first stage is planning, where educators create learning modules that incorporate character values to be instilled in students. The second stage is the execution phase, during which students are shaped to embody values such as religiosity, discipline, and responsibility both inside and outside the classroom. The behaviors exhibited by students in applying religious values include habits like performing the Dhuha prayer and other forms of worship. For discipline, students demonstrate punctuality in arriving at school, while responsibility is shown through students fulfilling their cleaning duties according to their schedules and not littering. Challenges faced by educators in implementing character education include a lack of parental support and difficulties for transfer students adjusting from their previous schools to SABIR. To address these challenges, educators have established good communication with parents and approached transfer students to help them adapt. The findings indicate that SABIR has successfully implemented character education within both classroom and outdoor learning environments, supported by programs that aid students in developing their character. The implementation of character-based education at SABIR can be considered effective; any shortcomings are addressed through solutions involving communication with parents and support for students.